The Development of Android-Based Mobile Learning Media (MLM) for Elementary School Students of Kendal Indonesia - ., Trimurtini; ., Liftiah; Ahmadi , Farid (KnE Social Sciences, 2019)
Learning Media is one of the essential aspects in creating a meaningful and good quality learning process. The use of mobile device in the learning process is called mobile learning (m-learning). It is deﬁned as a learning in which the learners are demanded to be active or moving to places by utilizing a mobile technology device. The existence of m-learning is indeed unable to substitute e-learning (electronic learning) let alone replacing face-to-face meeting in a class. M-learning is intended to complement the learning took place in a class. It also helps the students to re-learn the material they have not understood anywhere and anytime they want. This surely provides novel learning experience for the students. Developing Mobile Learning Media (MLM) is the alternatives in providing the most suitable and effective media in this era. The type of research used in this study is the developing method of SDLC (System Development Life Cycle) of Waterfall. According to the FGD conducted with elementaryteachersinKaliwunguDistrictKendal,thediscussionleadtotheneedupon android-based MLM was in mathematics subject. The researcher then developed the media with the materials that the students needed. This media had been validated by the experts of material, media, and children psychology. Based on the test conducted for the media, it presented that the media is feasible to be used. The try out for the Android-based MLM-media was limitedly administered to ten students of Fifth Grade and one teacher, and try out was conducted successfully and showed positive results. Keywords: android, e-learning, media, MLM (Mobile Learning Media)